Genotyping of Treponema pallidum in Cuba (2018-2019): Increased Circulation of Recombinant Genotype and No New Treponema pallidum Subspecies endemicum Infection Among Syphilis Patients - Noda, Angel A; Rodríguez, Islay; Šmajs, David (Sexually transmitted diseases, 2020)
OBJECTIVES: This study aimed to determine the allelic profiles of Treponema pallidum in patients confirmed with syphilis in Cuba (2018-2019) and to explore mutations leading to macrolide and tetracycline resistance. METHODS: Multilocus sequence typing and polymerase chain reaction of rrn loci (23S and 16S rDNA), followed by Sanger sequencing, were used to define the allelic profile of TPA and resistance mutations, respectively. RESULTS: Allelic profile 1.3.1 and the recombinant profile were identified, with 15.7.3 having an increased frequency. We did not detect the presence of the T. pallidum subspecies endemicum among syphilis patients, as in previous reports. A high frequency of macrolide-resistant strains and the absence of mutations potentially causing tetracycline resistance were found. CONCLUSIONS: Understanding the current status of treponemal infection in Cuban patients provides insights into the syphilis epidemiology.
Keywords: Syphilis; Macrolides; Cuba; Kuba; lidé; Treponema pallidum; Genotype; makrolidy; syfilis; genotyp; Humans